Breaking the sound barrier: A critical anthology of the new music - Battock, Gregory (New York Elsevier Dutton Publishing Co., 1981)
An anthology of writings re New Music - ie: mostly 20th century 'avant-garde' classical music - edited by Gregory Battcock.